2003
DOI: 10.1097/01.prs.0000046608.52722.89
|View full text |Cite
|
Sign up to set email alerts
|

Arterial Reconstruction Using the Basilic Vein from the Zone of Injury in Pediatric Supracondylar Humeral Fractures: A Clinical and Radiological Series

Abstract: The authors describe the advantages of using the basilic vein as an arterial conduit in the management of children with supracondylar humeral fractures requiring vascular repair. Eight children, aged 3 to 10 years, presented with supracondylar humeral fractures and vascular injury. In all eight children, the arteries were successfully reconstructed with a reversed, interposition basilic vein graft harvested from the ipsilateral arm. The basilic vein was anatomically consistent with few side branches and was an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
21
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 21 publications
0
21
0
Order By: Relevance
“…4,9 More than 95% of these fractures are displaced in extension, which may lead to a variety of neurological and vascular complications. 1 In this series all the supracondylar fractures were extension type and the mechanism of injury was falling on the outstretched arm. Louahem et al 15 reported that 29 patients (14%) out of 210 children suffering from severely displaced supracondylar fracture humerus had vascular complications.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…4,9 More than 95% of these fractures are displaced in extension, which may lead to a variety of neurological and vascular complications. 1 In this series all the supracondylar fractures were extension type and the mechanism of injury was falling on the outstretched arm. Louahem et al 15 reported that 29 patients (14%) out of 210 children suffering from severely displaced supracondylar fracture humerus had vascular complications.…”
Section: Discussionmentioning
confidence: 97%
“…Louahem et al 15 reported that 29 patients (14%) out of 210 children suffering from severely displaced supracondylar fracture humerus had vascular complications. Skaggs and Pershad 1,16 reported that the incidence of vascular injury of displaced supracondylar fractures has ranged from 3 to 12% of patients. Campbell et al 6 reported that 38% of their cases had evidence of injury to the brachial artery.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations